Ornamentation and Modern Architecture in Iraq (Journal of Engineering, 2019)
Despite the history of Baghdad city extends into a long history, most of the contemporary buildings of Baghdad have been shaped in the era of modernity. Furthermore, most of the buildings of modernity in Baghdad are types of modernity buildings in Iraq as a whole, and due to all the joints of change and development are taking place in Iraq starts from Baghdad. Accordingly, all selected buildings, which would be presented as case studies of modernity will be exclusively in Baghdad. Although the importance of this significant modernist product, which represents the identity of Baghdad, which should be preserved by the renewal and preservation policies, the problem of research was emerged as follow: new finishing materials have been used to cover their exterior facades, which are unrelated to the notion of modernity.The aim of this research is highlighting this Phenomena, which occurred after 2003 in Iraq, and characterized by changing the monuments of modernity buildings. This change was either by undergoing a lot of changes of their facades design or by covering them with new materials. Thus, the use of these materials, specifically plates of aluminum will be analyzed and then, discussed the effects implications, since these buildings represent a cultural and architectural heritage that establishes architectural successes. Consequently, the research methodology will depend on the choice of buildings that built in an important era (between 1950s and 1960s), analysis their facades before and after changes, in order to identify the reasons that resulted to the usage of such materials and suggest recommendations, which can address their negative impacts.